New directions in the Australian house - Johnson, Anna (2006)
Twenty-five residential projects which demonstrate a unique Australian diversity of character and which share an expressive form of monumentalism with both modern and abstract elements have been compiled for this publication. Each house is extensively photographed and accompanied by sections and plans. John Wardle, Alex Popov, Allan Powell, Wood Marsh and Neeson Murcutt are some of the practices featured among others.